2000
DOI: 10.1081/ddc-100101309
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Floating Dosage Forms of Furosemide: In Vitro and In Vivo Evaluations of Bilayer Tablet Formulations

Abstract: For the purpose of enhancement the bioavailability of furosemide (FR), a floating dosage form with controlled release of FR was designed in this study. Because of the lower solubility of active material in the gastric medium, it was first enhanced by preparing an inclusion complex of FR with beta-cyclodextrin (beta-CD) in a 1:1 proportion using the kneading method. Following the design of dosage form, bilayer floating tablets were prepared. After dissolution rate studies were performed using the continuous flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
47
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 14 publications
0
47
0
1
Order By: Relevance
“…Higher absolute bioavailability in a floating dosage form than from a nonfloating commercial product of furosemide has already been demonstrated in dogs [4]. Improved bioavailability of furosemide from a floating tablet in human volunteers has also been reported [5]. Although single unit dosage forms of furosemide have been extensively investigated, few studies have been reported using multiple unit dosage forms of furosemide [6].…”
Section: Introductionmentioning
confidence: 99%
“…Higher absolute bioavailability in a floating dosage form than from a nonfloating commercial product of furosemide has already been demonstrated in dogs [4]. Improved bioavailability of furosemide from a floating tablet in human volunteers has also been reported [5]. Although single unit dosage forms of furosemide have been extensively investigated, few studies have been reported using multiple unit dosage forms of furosemide [6].…”
Section: Introductionmentioning
confidence: 99%
“…It then remains buoyant and floats in the gastric fluid, affecting a prolonged gastric residence time (GRT). This floating dosage form is known as a hydrodynamically balanced system (HBS (Ozdemir et al 2000).Hydrodynamically balanced systems can remain in the gastric region for several hours and hence significantly prolong the gastric residence time of drugs. Prolonged gastric retention improves bioavailability, reduces drug waste, and improves solubility for drugs that are less soluble in a high pH environment of small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…From this the requisites to prolong the residence time of such dosage forms in the stomach leads to an important approach including decrease in the density to stimulate floating in the gastric fluids and thus gastro-retentive sustained release dosage form is reached. 2 This new revolution that has been achieved in sustained drug delivery system represents today by floating in situ gel system. In this system, a solution of low viscosity can be easily applied; which upon reaching gastric contents it undergoes polymeric changes; thus producing a viscous in situ gel of density lower than the gastric fluids.…”
Section: Introductionmentioning
confidence: 99%